Pariah in the world economy: How should countries respond to Argentina's return to economic nationalism? - Lisa Brandt; Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2013)
Assessing Argentina's trade and investment policies, this Policy Brief discusses possible strategies for the European Union and the international community to respond to Argentina's turn to economic nationalism. The intention of the Argentinean government to strengthen national industries and stabilise its current accounts has led to irrational policies and irresponsible behaviour. Its manifest disrespect for international agreements and rules on trade and investment stretches from import restrictions and licencing schemes to impulsive nationalisation of companies. The European Union should not turn a blind eye to Argentina's misbehaviour. Indeed, the economic power relations might induce the EU to retaliate with protective measures targeting Argentinean exports. However, such a tit-for-tat approach is unlikely to incentivise Argentina to cease its provocative misconduct. Together with other major economies, the EU should instead use the legal and diplomatic tracks in order to defend the economic interests of its companies and industries. The EU should exhaust the legal mechanisms in the framework of the WTO and the ICSID and not retaliate against Argentina unless such measures have been sanctioned by international bodies beforehand. In parallel, diplomatic efforts should be intensified in order to reason with Argentina. Ultimately, it is up to Argentina whether or not it prefers to continue to act in violation of the international agreements that it has voluntarily ratified. Unless Argentina displays a greater interest in engaging in constructive dialogue and respect for the rules, there is no point in inviting it to meetings and work processes relating to international economic cooperation, such as the G20. Similarly, if Argentina continues to flaunt its obligations in the IMF, it should not remain as member.
Keywords: 330; Wirtschaftsnationalismus; Wirkungsanalyse; Argentinien